2014
DOI: 10.1128/jvi.02477-13
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Entry Phenotypes of Macrophage-Tropic HIV-1 across a Wide Range of CD4 Densities

Abstract: Defining a macrophage-tropic phenotype for HIV-1 to assess a role in pathogenesis is complicated by the fact that HIV-1 isolates vary continuously in their ability to enter monocyte-derived macrophages (MDMs) in vitro, and MDMs vary in their ability to support HIV-1 entry. To overcome these limitations, we identified consistent differences in entry phenotypes between five paired blood-derived, T cell-tropic HIV-1 env genes, four of which are CCR5-using (R5) and one of which is CXCR4-using (X4), and cerebrospin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
152
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 102 publications
(161 citation statements)
references
References 68 publications
9
152
0
Order By: Relevance
“…It is tempting to speculate that HIV-1 will reach maximum infectivity near to its natural number of spikes of 7 to 14 spikes per virion and that a dense array of Env is unnecessary for maximum infectivity. A caveat, however, is that infectivity requirements can differ with the type of target cell, particularly with cells having low levels of CD4 (e.g., macrophages) (63), or in the case of Envs of low intrinsic infectivity (48,50,51). Additional studies to determine the infectivity of hVLPs in which target cells and envelopes are varied will therefore be informative.…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate that HIV-1 will reach maximum infectivity near to its natural number of spikes of 7 to 14 spikes per virion and that a dense array of Env is unnecessary for maximum infectivity. A caveat, however, is that infectivity requirements can differ with the type of target cell, particularly with cells having low levels of CD4 (e.g., macrophages) (63), or in the case of Envs of low intrinsic infectivity (48,50,51). Additional studies to determine the infectivity of hVLPs in which target cells and envelopes are varied will therefore be informative.…”
Section: Discussionmentioning
confidence: 99%
“…The dependence on receptor level for viral entry can now be demonstrated most convincingly using the Affinofile cell line, in which the surface density of CD4 and/or CCR5 can be experimentally manipulated (21). Using this approach, it has been possible to identify M-tropic viruses, most often isolated from the cerebrospinal fluid (CSF) of subjects late in disease, by their ability to efficiently enter cells with low CD4 densities (CD4 low cells) as a surrogate marker for macrophage tropism (14,22). Although it is possible to observe differences in entry phenotype using MDMs, it is difficult to account for the inherent variability among both the viruses and the cells in unequivocally assigning cellular tropism.…”
mentioning
confidence: 99%
“…Differences in how macrophage tropism is defined can lead to substantially different observations about M-tropic viruses. Although it is widely observed that M-tropic viruses are able to enter more efficiently at low CD4 densities (14,19,(22)(23)(24)(25)(26) and are more sensitive to neutralization by soluble CD4 (sCD4) (27)(28)(29) than T-tropic viruses, few other characteristics are widely agreed upon. Similarly, several amino acid changes in the HIV-1 Env protein have been associated with macrophage tropism (24,25,27,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), but the changes are not consistent across different subjects when macrophage tropism is defined as a distinct set of evolutionary variants within that subject (40).…”
mentioning
confidence: 99%
See 2 more Smart Citations